Expanding Water and Sanitation Services to Low-Income Households : the Case of the La Paz-El Alto Concession - Komives, Kristin; Brook Cowen, Penelope J. (World Bank, Washington, DC, 2012)
Bolivia is one of a growing number of developing countries turning to the private sector to improve urban water and sanitation services. The country's first major contract in the sector, a twenty-five-year concession for the neighboring cities of La Paz and El Alto, was implemented in August 1997. A primary objective in moving to a private concession was to expand services to low-income households while holding down costs by increasing efficiency. It is not a foregone conclusion that the new concessionaire will do a better job of expanding service; much will depend on how well the contract and sector regulation have been designed. Because the La Paz-El Alto concession was explicitly designed to expand service to the poor, this concession is a good case study for evaluating how different provisions in the contract and the sector regulation may help or hinder service expansion.